Perceived Parenting Styles, Social Competence, Bullying Victimization and Self-Injurious Behaviors among Adolescents in Pakistan - Momna Jameel (Research Journal of Psychology, 2025)
The cross-sectional study was conducted to explore the relationship among Perceived Parenting styles, Social Competence, Bullying Victimization among adolescents from the age range of 12 to 19 with the sample of 300 adolescents from different institutes of Sialkot, Pakistan (150 Male and 150 female)(M= 16.06, SD= 1.93).This research highlighted the correlation between these variables by using Perceived parenting styles scale (Nasir &Naeem, 2015), Social competence scale for adolescents (Khurshid &Mehmood, 2018), Bullying and victimization scale for adolescence (Amjad & Saleem, 2014) and Self-injurious behavior scale (Fariha & Saleem, 2017) along with the demographic variables. The results revealed that perceived parenting styles have negative relationship with the self-injurious behaviors and negative relationship between social competence and self-injurious behaviors in adolescents while on the other hand bullying victimization has positive relationship with the self-injurious behaviors moreover bullying victimization were high in males than females and in private institutes than Govt institutes while on the other hand warm and control parenting styles and social competence ware high in females than males and were high among Govt institutes adolescents than private institutes adolescents. The main goal of this study was to implicant the result findings to raise awareness about these issues to help the adolescents who are silently suffering from these issues and to raise awareness in society.